PENGARUH MODEL KOOPERATIF GALLERY WALK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA DITINJAU DARI SELF CONFIDENCE - Masyhur, Tenri Alang (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This study examines whether the mathematical communitical skills of studens taught with the gallery walk cooperative learning model are effective, reviewed from the self-confidence of students in grade VII at SMP Negeri 1 Botupingge. This Quasi Experiment research implements the treatment by level 2 x 2 design with a two-track analysis test and a Tukey test. The results obtain that the mathematical communication skills of students with high self-confidence in gallery walk cooperative learning are 79.86, and student with low self-confidence in direct learning are only 64.29. it can also be proven through tests with a significant level of 5% and df=33 showing tcount > tcount, 3.485, α=0.05, and ttable=2.042. in conclusion, the mathematics communication skills of student with high self=confidence that are taught by gallery walk cooperative learning are higher and more effective than students with low self-confidence that are taught by direct learning.